TOOLS FOR ACTIVATION OF INVESTMENT AND INNOVATION ACTIVITIES OF LOGISTICS ENTITIES - PANCHENKO, Volodymyr; PANCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article substantiates the basic provisions for the establishment and further activation of investment and innovation activities of logistics entities. The importance of building a management system for investment and innovation processes by logistics subjects, which will focus on the search for sources, external support, reliable partners and other things, which will involve the activation of investment in new applied developments, as a result of which the logistics subject is able to bring innovative products to the market (goods, services). The main areas of adjustment and activation of innovative activity of logistics entities are highlighted. The conditions that ensure the activation of innovative and innovative activities of logistics subjects are summarized. According to the toolkit, the activation of investment and innovation activity of logistics entities should be attributed to the establishment of self-financing of R&D, modernization of the material and technical base, expansion of the spheres of use of innovations, establishment and improvement of the information and analytical exchange system, implementation of the principle of participation in the management system of social and labor relations, formation internal motivational environment, modernization of the organizational and economic management system. The priority value of the toolkit for analyzing and forecasting the activation of innovative and innovative activities of logistics entities is substantiated. The elements of the management system for the activation of investment and innovation activities of business entities have been determined. It is proven that the development of investment management reflects a generalized theoretical understanding of the direction of investment development of logistics entities, the possibility of increasing the efficiency of business processes and strengthening their long-term competitiveness due to the development of new scientific and technical products.
Keywords: investment and innovation activity; logistics entity; activation; innovative products; technologies; financing; investment management